Effects of preferred vs. nonpreferred music on resistance exercise performance - Ballmann, C. G.; McCullum, M. J.; Rogers, R. R.; Marshall, M. R.; Williams, T. D. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to examine the effects of listening to preferred vs. nonpreferred music on resistance exercise performance. Twelve resistance-trained college-aged males (age = 20.5 ± 1.24 years, height = 183.9 ± 6.8 cm, and body mass = 97.0 ± 18.2 kg) were recruited for this study. In a within-groups counterbalanced study design, subjects either listened to preferred or nonpreferred music during a bench press exercise test. Subjects completed as many repetitions as possible at 75% of their 1 repetition maximum with maximum explosive intent. Power and velocity of the barbell movement was measured for the first 3 repetitions using a linear position transducer. Motivation was measured using a visual analog scale immediately after exercise. Each exercise trial was separated by a 48-hour washout period. Results indicate that listening to preferred music increased overall bench press repetitions completed (p = 0.005; effect size [ES] = 0.84). During the first 3 repetitions, mean velocity (p = 0.001; ES = 1.6), relative mean power (p = 0.012; ES = 0.55), peak velocity (p = 0.011; ES = 0.99), and peak power (p = 0.009; ES = 0.35) were higher while listening to preferred music vs. nonpreferred music. Finally, motivation during the lift (p < 0.001; ES = 5.9) was significantly higher while listening to preferred vs. nonpreferred music. Current findings suggest that listening to preferred music by the individual results in greater performance than nonpreferred during resistance exercise. Athletes may benefit from the option to listen to their preferred music to increase motivation and resistance exercise performance.